2000
DOI: 10.3168/jds.s0022-0302(00)74945-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computerized Mate Selection Programs to Control Inbreeding of Holstein and Jersey Cattle in the Next Generation

Abstract: The expected role of computerized mate selection programs with regard to inbreeding and lifetime profitability of Holstein and Jersey cattle was examined using data from 25 large registered herds of each breed. Sire selection and mate allocation were carried out using linear programming with the following objectives: 1) minimum inbreeding, 2) maximum net merit subject to a fixed inbreeding threshold, and 3) maximum expected lifetime profit after adjustment for inbreeding depression. Inbreeding of actual mating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 7 publications
4
43
0
1
Order By: Relevance
“…Although the Dairy Guzerat Breeding Program has been started recently (1994) and the sex ratio is increasing (Table 1), these results might be due to the introduction of sires of other origins and proposals, e.g. from the beef herds, into the herds by artificial insemination rather than the use of sires from the herd itself, in addition to the planned mating practice carried out in most herds (Weigel and Lin, 2000;Caballero and Toro, 2002;Colleau et al, 2004). Mating plans that minimize coancestry among pairs represents a robust tool to maximize N e (Caballero and Toro, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the Dairy Guzerat Breeding Program has been started recently (1994) and the sex ratio is increasing (Table 1), these results might be due to the introduction of sires of other origins and proposals, e.g. from the beef herds, into the herds by artificial insemination rather than the use of sires from the herd itself, in addition to the planned mating practice carried out in most herds (Weigel and Lin, 2000;Caballero and Toro, 2002;Colleau et al, 2004). Mating plans that minimize coancestry among pairs represents a robust tool to maximize N e (Caballero and Toro, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A simulation study based on Zebu MOET nucleus population parameters reported a trend of increasing inbreeding coefficients along selection generations due to the high frequency of mating among related animals (Peixoto et al, 2005). Weigel and Lin (2000) and Colleau et al (2004) stated that mating plans are an important tool to manage genetic variability. Furthermore, the effects of inbreeding depression may decrease animal fertility and survival, as well as the rate of genetic progress (Falconer and Mackay, 1996;Hill, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Weigel and Lin (2002) used the method of Meuwissen (1997) and constrained the level of inbreeding in the next generation and found that the optimal number of bull sires and bull dams decreased as the inbreeding constraint increased, particularly at low levels of inbreeding. Weigel and Lin (2000) compared the weighted mean lifetime net merit and the weighted mean adjusted lifetime net merit of the selected group. The weighted mean lifetime net merit after adjustment to zero using a cost factor of $23 per 1% inbreeding as proposed by Smith et al (1998) was highest at an intermediate level of inbreeding.…”
Section: Optimum Genetic Contributionsmentioning
confidence: 99%
“…Kadlečík et al (2004) evaluated alternatives of breeding program in the Slovak Pinzgau population according to the achieved level of inbreeding. Effective tools dealing with and managing inbreeding in cattle populations providing a given genetic gain at a fixed inbreeding rate by optimizing long-term genetic contributions of ancestors were presented by Bijma and Wooliams (1999) or Weigel and Lin (2000). Long-term selection responses in dairy herds were also compared by Šafus and Přibyl (2005).…”
mentioning
confidence: 99%